Scenario analysis on road transport service: Energy consumption and GHG emissions - Hue, Pham Thi; Tuyet, Nguyen Thi Anh; Co, Hoang Xuan (Vietnam Journal of Science and Technology, 2021)
The aim of this study is to evaluate energy consumption and greenhouse gas (GHG) emissions from Vietnam’s road transport service through establishing scenarios in 2015-2050. Four scenarios are firstly developed toward improving energy efficiency, floating automotive industry strategy and then energy demands, GHG emissions for road transport in these scenarios are estimated. Transport demand, technology penetrative rate, fuel type, fuel economy, emission standard and influence of other factors on emissions are bases of the selected input data. Calculator 2050 is used as a support tool of interface and calculation. The results are shown as following: Energy consumption and GHG emissions of road transport service will reach 11.28 Mtoe and 32.07 MtCO2e in 2030 as well as 36.95 Mtoe and 105.04 MtCO2e in 2050 in basic scenario, respectively, with annual average growth rate reach 6.4%. The contribution to increasing the energy consumption and GHG emissions of freight transport service is higher than that of passenger transport service. In the best case, energy consumption and GHG emissions are reduced by 27.4%, 30.3% in 2030 and 37.8%, 50.7% in 2050 compared to the basic scenario. This reduction is mainly due to the use of alternative fuels/vehicles in these activities.